Sexual dimorphism in sister species of Leucoraja skate and its relationship to reproductive strategy and life history. Issue 2 (13th January 2016) - Martinez, Christopher M.; Rohlf, F. James; Frisk, Michael G.
SUMMARY: Instances of sexual dimorphism occur in a great variety of forms and manifestations. Most skates (Batoidea: Rajoidei) display some level of body shape dimorphism in which the pectoral fins of mature males develop to create a distinct bell‐shaped body not found in females. This particular form of dimorphism is present in each of the sister species Leucoraja erinacea and Leucoraja ocellata, but differences between sexes are much greater in the former. In order to understand the nature and potential causes of pectoral dimorphism, we used geometric morphometrics to investigate allometry of fin shape in L. erinacea and L. ocellata and its relationship to the development of reproductive organs, based on previous work on the bonnethead shark, Sphyrna tiburo . We found that allometric trajectories of overall pectoral shape were different in both species of skate, but only L. erinacea varied significantly with respect to endoskeleton development. Male maturation was characterized by a number of sex‐specific morphological changes, which appeared concurrently in developmental timing with elongation of cartilage‐supported claspers. We suggest that external sexual dimorphism of pectoral fins in skates is a byproduct of skeletal growth needed for clasper development. Further, the magnitude of male shape change appears to be linked to the differential life histories of species. This work reports for the first time that pectoral dimorphism is a persistent feature in rajoid fishes, occurring in varying degrees across several genera. Lastly, our results suggest that pectoral morphology may be useful as a relative indicator of reproductive strategy in some species.